ANALISIS SEBARAN LOGAM BERAT PADA ALIRAN AIR DARI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH AIR DINGIN - -, Fatmawinir; Suyani, Hamzar; Alif, Admin (Universitas Andalas, 2015)
Final Disposal of waste at Air Dingin Padang City using open dumping system is expected to negatively affect the groundwater and surrounding waterways. Research on the content of heavy metals in landfill water flow in the Air Dingin were made in 2 (two) times that were before the rain and after the rain, then the results were compared with the applicable standard. The content of heavy metals Pb, Cu, Zn, Cd and Mn in Final Disposal (TPA) of waste at Air Dingin Padang City were 0.01-0.17 mg/L, 0.005-0.025 mg/L, 0.0-0.7254 mg/L, 0.0-0.011 mg/L, dan 0.0-0.966mg/L. Pb concentration exceeded the quality standard KEPMEN LH 51 in 1995 leachate pond, while the flow of water and monitoring wells Pb metal content exceeds the quality standards PP.RI.No.82 on 2001 and Mn outlet river exceeds the quality standards PP.RI.No.82 on 2001. In population of all heavy metals well below the quality stanadard PP.RI.No.82 on 2001. The content heavy metals was affected by the distance of the location of waste, the pH value and after of the rain water around the landfill waste.